Kemampuan Guru dalam Merancang Modul Ajar Bilingual pada Kurikulum Merdeka di Sekolah Dasar - Ardani, Alvina Verda; Nurmala, Amalia; Aini, Intan Nur; Azizah, Wafiyatul 'Ahdi Noor; Az Zahra, Hayya Fathimah; Zainiyah, Yiyin Syifa; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine teachers’ ability to design bilingual teaching modules within the framework of the Merdeka Curriculum at the elementary school level. The research employs a literature review method with a qualitative approach, in which data were obtained through an analysis of relevant national and international journals. The findings indicate that the success of designing bilingual teaching modules depends on teachers’ understanding of five key aspects: analysis of student, teacher, and school conditions; identification of the Pancasila Student Profile; formulation of Learning Objective Pathways (ATP); development of module components; and evaluation and follow-up. Challenges faced by teachers include limited foreign language proficiency, lack of training, and the absence of adequate technical guidelines. Therefore, continuous training and mentoring are essential to enable teachers to create effective, contextual bilingual teaching modules that support the achievement of the Merdeka Curriculum goals and the Pancasila Student Profile.